Assessment of failure toughening mechanisms in continuous glass fiber thermoplastic laminates subjected to cyclic loading. (15th March 2019) - Nikforooz, M.; Montesano, J.; Golzar, M.; Shokrieh, M.M.
Abstract: Tensile fatigue behaviour of glass fiber/polyamide composites, including unidirectional ([0]8, [90]8 ) and cross-ply ([02 /902 ]s, [04 /904 ]s and [904 /04 ]s ) laminates, was studied and compared to that of similar glass fiber/epoxy composites. The fatigue resistance of cross-ply glass/polyamide was greater than that of glass/epoxy while also exhibiting lower stiffness reduction. To explain this key observation, residual stiffness and residual strength fatigue tests were performed on cross-ply laminates, while optical microscopy was used to measure ply crack density during the different stages of cycling. Testing of the cross-ply laminates at lower peak stresses of 50% of the ultimate tensile strength (i.e., high cycle fatigue regime) revealed partial cracks that did not propagate completely through the width and thickness of plies due to high matrix toughness and other observed toughening mechanisms such as matrix bridging. A micromechanical finite element model with explicit ply cracks was also used to predict laminate stiffness degradation corresponding to observed ply crack densities, revealing that stiffness degradation was overpredicted when cracks were assumed to span the entire specimen width. Additional finite element simulations with partial cracks showed notably less stiffness reduction. These observations suggest glass/polyamide is inherently more damage tolerant than glass/epoxy and may be a suitable replacement for fatigue critical structures.